Retinal Vascular Endothelial Growth Factor Induces Intercellular Adhesion Molecule-1 and Endothelial Nitric Oxide Synthase Expression and Initiates Early Diabetic Retinal Leukocyte Adhesion in Vivo - Joussen, Antonia M. (American Society for Investigative Pathology, 2002)
Leukocyte adhesion to the diabetic retinal vasculature results in early blood-retinal barrier breakdown, capillary nonperfusion, and endothelial cell injury and death. Previous work has shown that intercellular adhesion molecule-1 (ICAM-1) and CD18 are required for these processes. However the relevant in vivo stimuli for ICAM-1 and CD18 expression in diabetes remain unknown. The current study investigated the causal role of endogenous vascular endothelial growth factor (VEGF) and nitric oxide in initiating these events. Diabetes was induced in Long-Evans rats with streptozotocin, resulting in a two- to threefold increase in retinal leukocyte adhesion. Confirmed diabetic animals were treated with a highly specific VEGF-neutralizing Flt-Fc construct (VEGF TrapA(40)). Retinal ICAM-1 mRNA levels in VEGF TrapA(40)-treated diabetic animals were reduced by 83.5% compared to diabetic controls (n = 5, P < 0.0001). VEGF TrapA(40) also potently suppressed diabetic leukocyte adhesion in retinal arterioles (47%, n = 11, P < 0.0001), venules (36%, n = 11, P < 0.0005), and capillaries (36%, n = 11, P < 0.001). The expression of endothelial nitric oxide synthase (eNOS), a downstream mediator of VEGF activity, was increased in diabetic retina, and was potently suppressed with VEGF TrapA(40) treatment (n = 8, P < 0.005). Further, VEGF TrapA(40) reduced the diabetes-related nitric oxide increases in the retinae of diabetic animals. The inhibition of eNOS with N-ω-nitro-l-arginine methyl ester also potently reduced retinal leukocyte adhesion. Although neutrophil CD11a, CD11b, and CD18 levels were increased in 1-week diabetic animals, VEGF TrapA(40) did not alter the expression of these integrin adhesion molecules. Taken together, these data demonstrate that VEGF induces retinal ICAM-1 and eNOS expression and initiates early diabetic retinal leukocyte adhesion in vivo. The inhibition of VEGF bioactivity may prove useful in the treatment of the early diabetic retinopathy.